1983
DOI: 10.1103/physrevb.27.5032
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous silicon-carbon-fluorine alloy films

Abstract: A new amorphous semiconductor alloy system Si"C"F~has been prepared by rf sputtering of polycrystalline SiC in an Ar+SiF4 atmosphere. Dark conductivity and optical absorption of thin films are measured as functions of F concentration. Infrared spectra indicate a preferential attachment of fluorine to carbon over silicon. The bonded fluorine concentration is estimated to be as high as 40 at. %. The principal reststrahlen band shifts to higher frequencies and appears to sharpen with the increase of fluorine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
1
8
1
3
Order By: Relevance
“…As the amount of CF 4 is increased in the feed gas, the stress decreases. Similar trends have been observed with other amorphous films (such as SiO2, 8 impurities, and energetic ion bombardment are often cited as the causes of the compressive stress.…”
Section: Fig 13 Procedures For Estimating Absorption Coefficientssupporting
confidence: 76%
“…As the amount of CF 4 is increased in the feed gas, the stress decreases. Similar trends have been observed with other amorphous films (such as SiO2, 8 impurities, and energetic ion bombardment are often cited as the causes of the compressive stress.…”
Section: Fig 13 Procedures For Estimating Absorption Coefficientssupporting
confidence: 76%
“…It is apparent that the growth of μc-Si at this stage is suppressed in the films deposited with a high flow of methane in the two top spectra; this is explained by the fact that the C-H bonds have higher bond energy than their Si-H counterparts, which promotes a better thermal stability of the films with respect to hydrogen effusion.. The spectra of the films annealed at 900 °C are characterized by a sharp prominent peak at 520 cm -1 due to crystalline Si and a small broad peak centred around 960 cm -1 attributed to 3C-SiC LO phonons [15,16].…”
Section: Structural Propertiesmentioning
confidence: 95%
“…1 Silicon carbide films deposited by plasmabased techniques present high hardness, high temperature stability and low friction coefficients. [7][8][9][10] However, the potential of fluorinated a-SiC:H films for protective coating applications has not been extensively examined. 6 Furthermore, the incorporation of fluorine leads to improved electronic properties by saturating dangling bonds.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, the incorporation of fluorine leads to improved electronic properties by saturating dangling bonds. 7 In particular, Miyake et al investigated the tribological properties of a-Si 0.4 C 0.6 :H films deposited using the electron cyclotron resonance ͑ECR͒ technique followed by fluorination by CF 4 plasma treatment. Some previous works reported that incorporation of fluorine in a-SiC:H films reduces the internal stress 11 and leads to higher thermal stability.…”
Section: Introductionmentioning
confidence: 99%